Польскiя аспекты ранняй творчасцi Maкcima Танка - Czykwin, Jan (Acta Polono-Ruthenica, 2008)
The article shows on the basis of his three collections of poetry the firm profound relationship of the Belorussian poet with the Polish culture, and simultaneously the fervent opposition of the poetical word to the Polish policy of denationalizing on grounds of Western Belorussia.